2011
DOI: 10.1111/j.1440-1754.2011.02244.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for community‐acquired pneumonia in pre‐school‐aged children

Abstract: Lower quality living environments increase the risk of pneumonia and hospitalisation with pneumonia in New Zealand. Poorer nutritional status may also increase the risk of pneumonia. Improving housing quality, decreased cigarette smoke exposure and early childhood nutrition may reduce pneumonia disease burden in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 46 publications
2
66
3
5
Order By: Relevance
“…Surprisingly, we did not observe any significant relationship between housing conditions and severity of CAP among the studied subjects ( P > 0.05 ), which was contrary to our expectations and to previous findings of Grant et al, who reported that lower quality living environments increase the risk of CAP and that improving housing quality may reduce the burden of CAP in New Zealand [23]. However, reporting in our study may have been unreliable, and a study to cover an extended population is recommended to better assess housing quality in the Nile Delta of Egypt, both in rural and urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, we did not observe any significant relationship between housing conditions and severity of CAP among the studied subjects ( P > 0.05 ), which was contrary to our expectations and to previous findings of Grant et al, who reported that lower quality living environments increase the risk of CAP and that improving housing quality may reduce the burden of CAP in New Zealand [23]. However, reporting in our study may have been unreliable, and a study to cover an extended population is recommended to better assess housing quality in the Nile Delta of Egypt, both in rural and urban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Respiratory failure, sepsis and cardiac complication are considered the most important direct causes of death among patients with pneumonia [3,4]. Risk factors for acquiring pneumonia were clearly detected by previous studies [5,6]. However, there are lack of studies that investigate risk factors and predictors for poor pneumonia outcome in children.…”
Section: Introductionmentioning
confidence: 97%
“…This difference may be due to our approach of obtaining blood cultures on all patients rather than selectively in patients perceived to be more severely ill. 3,4,6,[27][28][29][30] This may be a closer estimate of the true rate of bacteremia in admitted patients with CAP.…”
Section: Discussionmentioning
confidence: 99%